Capital markets, financial markets and social capital (an essay on economic theory and economic ideas) - Thomas, Clive Y. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Focuses on the complementarities and synergies between social adjustment, the pursuit of macroeconomic balance, and the growth and development of Caribbean economies.